Itaconate is a covalent inhibitor of the Mycobacterium tuberculosis isocitrate lyase. Issue 1 (19th October 2020) - Kwai, Brooke X. C.; Collins, Annabelle J.; Middleditch, Martin J.; Sperry, Jonathan; Bashiri, Ghader; Leung, Ivanhoe K. H.
Abstract : Mycobacterium tuberculosis isocitrate lyases (ICLs) form a covalent adduct with itaconate through their catalytic cysteine residue. These results reveal atomic details of itaconate inhibition and provide insights into the catalytic mechanism of ICLs. Abstract : Itaconate is a mammalian antimicrobial metabolite that inhibits the isocitrate lyases (ICLs) of Mycobacterium tuberculosis . Herein, we report that ICLs form a covalent adduct with itaconate through their catalytic cysteine residue. These results reveal atomic details of itaconate inhibition and provide insights into the catalytic mechanism of ICLs.